Analysis of a cohort of 101 CDAII patients: description of 24 new molecular variants and genotype‐phenotype correlations. (29th July 2016) - Bianchi, Paola; Schwarz, Klaus; Högel, Josef; Fermo, Elisa; Vercellati, Cristina; Grosse, Regine; van Wijk, Richard; van Zwieten, Rob; Barcellini, Wilma; Zanella, Alberto; Heimpel, Hermann
Summary: Congenital dyserythropoietic anaemia type II (CDAII) is a rare autosomal recessive disease characterized by ineffective erythropoiesis, haemolysis, erythroblast morphological abnormalities, hypoglycosylation of some red blood cell membrane proteins, particularly band 3, and mutations in the SEC23B gene. We report the analysis of 101 patients from 91 families with a median follow‐up of 23 years (range 0–65); 68 patients are newly reported. Clinical and haematological parameters were separately analysed in early infancy and thereafter, when feasible. Molecular analysis of the SEC23B gene confirmed the high heterogeneity of the defect, leading to the identification of 54 different mutations, 24 of which are newly described. To evaluate the genotype‐phenotype correlation, patients were grouped according to their genotype (two missense mutations vs. one missense/one drastic mutation) and assigned to two different severity gradings based on laboratory data and on therapeutic needs; by this approach only a weak genotype‐phenotype correlation was observed in the analysed groups.